2013
DOI: 10.1111/jam.12137
|View full text |Cite
|
Sign up to set email alerts
|

Bioactives from probiotics for dermal health: functions and benefits

Abstract: SummaryProbiotics have been extensively reviewed for decades, emphasizing on improving general gut health. Recently, more studies showed that probiotics may exert other health-promoting effects beyond gut well-being, attributed to the rise of the gut-brain axis correlations. Some of these new benefits include skin health such as improving atopic eczema, atopic dermatitis, healing of burn and scars, skin-rejuvenating properties and improving skin innate immunity. Increasing evidence has also showed that bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 91 publications
0
76
1
7
Order By: Relevance
“…an improvement to the innate immunity of the skin [23]. Likewise, administering during pregnancy and early infancy can reduce the risk of eczema developing [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…an improvement to the innate immunity of the skin [23]. Likewise, administering during pregnancy and early infancy can reduce the risk of eczema developing [20].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, administering during pregnancy and early infancy can reduce the risk of eczema developing [20]. More recently, topical application of probiotics and bacterial composites such as the cellular wall, its metabolites and dead bacteria has also been shown to produce certain immunity responses in the skin and to improve and reinforce the skin barrier [23][24][25].In cases of AD selective defects exist in the expression of the multiple genes which codify the corneal layer of the skin, including the filaggrin or the loricrin which only show 2% of the normal level, with structural alterations and a reduction in the corneocytes and the intercellular lipids. As a result, the whole process of terminal differentiation of the keratinocytes (cytoplasmic compaction, cornification and the release of lipids) necessary for the establishment of the barrier function is defective [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the probiotics are lactic bacteria belonging to Lactobacillus and Bifidobacterium, as well as other bacterial genera and yeasts (e.g., Saccharomyces) [1,3,4,7,51]. The prophylactic effect of probiotics has been reported and encouraged after surgery to prevent Clostridium difficile infection [2].…”
Section: Probioticsmentioning
confidence: 99%
“…In the last few years, however, there have been reports on the potential use of probiotics on the skin [7,51,53]. It has been suggested that probiotics ingested orally exerted their effects on the skin via mechanisms initiated in the gut, mostly due to changes in systemic immune responses such as modulating specific T-cells and stimulating toll-like receptors [4,7,31,47].…”
Section: Probiotics and Skin Carementioning
confidence: 99%